THE INFLUENCE OF ATORVASTATIN ON OMENTIN-1 LEVEL AND INSULIN RESISTANCE IN PATIENTS WITH CORONARY ARTERY DISEASE AND OBESITY - T. А. Maksymets (Vіsnik Naukovih Doslіdžen', 2018)
Adipose tissue is a powerful endocrine organ, which synthesizes significant amount of biologically active substances – adipokines. Due to adipokine dysfunction, a spectrum of diseases associated with obesity appears, namely, coronary artery disease, diabetes mellitus, hypertension and oncology. Hyperinsulinemia and insulin resistance play a significant role in pathogenesis of cardiometabolic complications in patients with obesity. They trigger a pathological cascade of reactions leading to cardiovascular diseases. Omentin-1 possesses anti-atherogenic action and it can modify peripheral effects of insulin.